Special Education Teachers’ Perceptions of Their Preparedness to Teach Students With Severe Disabilities in Inclusive Classrooms: A Saudi Arabian Perspective - Rashed Aldabas (SAGE Open, 2020)
Successful inclusive education for students with severe disabilities (SD) relies on the preparedness of their teachers. This descriptive study investigated special education teachers’ perceptions of their preparedness to teach students with SD in inclusive educational settings. A survey was sent to 382 teachers of such students. In general, findings indicate that participants were confident that they were prepared to teach students with SD in inclusive education. Findings also show that the lowest levels of confidence were reported by participants with the shortest working experience, participants who have taught students with moderate and severe intellectual disabilities and those with multiple disabilities, participants who have taught in the lower grades, and those who have already taught in general classrooms. The practical implications of the findings are discussed for supporting successful implementation of inclusive education for students with SD in terms of improving special education teachers’ preparedness.